(untitled) (Al-Academy, 2015)
Dealing with this study to find a link principle in the construction of the system and disorder to the promise of the principles and concepts of intellectual and philosophical form and content in the act of interior design of the halls education in the Ministry of Labor and Social Affairs , which leads to a reaction design objective and functionally and to increase the strength of the effect on users of the coaches and trainers . As it informs the side cognitive and developmental study of the design of the interior spaces . So it was the goal of research in the detection of the nature of the system and disorder with Focus indicators and the type of regulations and privacy and what constitutes the framework of knowledge in order to explain it through the procedures of this search for halls education in the Ministry of Labor and Social Affairs, with regard to the shape and content in these halls , as well as the importance of research and identify terminology .The second chapter includes theoretical framework , which included two sections the first section focuses on the concept of the system and disorder , and the second section focused on the expressive implications of form and content . Indicators were extract relied upon analysis of axles form . The third chapter was devoted to research procedures where followed a researcher descriptive approach and from the case study (Case - Study) through the analysis of three spaces belonging to the department of vocational training at the Ministry of Labor and Social Affairs , namely: ( a hall for English language teaching and workshop for air conditioning and refrigeration workshop art of cutting and sewing ) . Among the most prominent findings by the researcher are: Deficiencies in the recruitment of the foundations of interior design in these spaces led to the loss of tensile property and visual attraction , which is reflected in the decline in the proportion of common sense of the formal organization of the space , which led to disorder in the functional and aesthetic side of those spaces .As one of the most important conclusions reached by the researcher is that the organization , coordination and arrangement, is basically a requirement to coordinate the flow of movement that have impact on the success of the functionSpace.